FEMINIST DISCOURSE IN BUCHI EMECHETA'S NOVELS: A COMPARATIVE ANALYSIS OF DOUBLE YOKE AND GWENDOLEN (International Journal of Food and Nutritional Sciences, 2022)
In the realm of Nigerian literature, Buchi Emecheta stands as a beacon of feminist thought, supporting the voices of women. Her literary legacy encompasses a profound exploration of the struggles and triumphs of Nigerian women, transcending cultural boundaries and challenging entrenched patriarchal structures.Through an analysis of Emecheta's Double Yoke and Gwendolen, this study delves into the intersecting themes present in both novels, highlighting the complexities of gender dynamics, societal expectations, and the resilience of women in the face of adversity. By examining the narratives of characters like Nko and Gwendolen, this analysis seeks to shed light on Emecheta's contribution to feminist discourse and the enduring relevance of her works in contemporary literary studies. Furthermore, Emecheta's exploration of societal expectations sheds light on how gender, class, and cultural traditions overlap. By examining how characters like Nko and Gwendolen navigate these intersections, this analysis reveals the ways in which women challenge and redefine traditional gender roles.